2015
DOI: 10.1245/s10434-014-4326-x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Reconstruction of the Radiated Breast: Recent Trends Contrary to Traditional Standards

Abstract: BACKGROUND Immediate, implant-only breast reconstruction is traditionally discouraged in patients who receive radiation. It is not clear however, whether this widely-recognized mantra of breast reconstruction is observed in practice. The aim of this study is to evaluate reconstruction trends and practices in patients who have undergone mastectomy and radiation therapy. METHODS Female patients with unilateral breast cancer who required radiation in addition to mastectomy were extracted from the Surveillance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 37 publications
4
61
0
6
Order By: Relevance
“…A population-based SEER database study of 5481 radiated patients reported that the proportion of IBRs almost doubled (14% to 25%) over the decade of 2000 [59]. Interestingly, the annual increase in the rates of reconstruction among radiated patients was steeper than that in non-radiated ones for both implants (15% versus 11%), as well as flap-based reconstructions (8% versus 6%).…”
Section: Radiotherapy and Immediate Breast Reconstructionmentioning
confidence: 99%
“…A population-based SEER database study of 5481 radiated patients reported that the proportion of IBRs almost doubled (14% to 25%) over the decade of 2000 [59]. Interestingly, the annual increase in the rates of reconstruction among radiated patients was steeper than that in non-radiated ones for both implants (15% versus 11%), as well as flap-based reconstructions (8% versus 6%).…”
Section: Radiotherapy and Immediate Breast Reconstructionmentioning
confidence: 99%
“…Using the SEER database, Agarwal and colleagues evaluated immediate reconstruction trends among radiated patients and found a steady increase in implant only reconstruction from 27% to 52%, with a concomitant decrease in autologous reconstruction from 56% to 32%over the past decade (9). There are concerns about the outcomes of implant reconstructions in patients who have a history of radiation or require post-mastectomy radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…4-6 Despite these drawbacks, increasing numbers of immediate implant reconstructions are performed in unfavorable scenarios, albeit with a greater risk profile, because of the absent donor site morbidity. 7-9 There is also the potential benefit of early breast mound restoration especially for a patient threatened by a curtailed lifespan. Finally, once radiation has been completed, expansion cannot reliably be performed thereby eliminating prosthetic methods as an option for many patients.…”
Section: Introductionmentioning
confidence: 99%